2005
DOI: 10.1016/j.femsec.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and vertical distribution of magnetotactic bacteria along chemical gradients in freshwater microcosms

Abstract: The vertical distribution of magnetotactic bacteria along various physico-chemical gradients in freshwater microcosms was analyzed by a combined approach of viable cell counts, 16S rRNA gene analysis, microsensor profiling and biogeochemical methods. The occurrence of magnetotactic bacteria was restricted to a narrow sediment layer overlapping or closely below the maximum oxygen and nitrate penetration depth. Different species showed different preferences within vertical gradients, but the largest proportion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
125
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 50 publications
(65 reference statements)
7
125
0
1
Order By: Relevance
“…In equilibrium conditions, cells showed a reversal frequency of 0.126 s À 1 or less, which is low compared with data reported for non-MTB [40][41][42][43] . Consistent with the adaptation of MTB for growth in redox gradients in stratified sediments 27 , and also with the dependence of oxygen-sensitive magnetite biomineralization and N 2 fixation on suboxic conditions 44,45 , we found a higher proportion of cells swam faster and reversed less frequently under microoxic than under anoxic or fully oxic conditions. The model of energy taxis suggests cells swimming towards lower or higher oxygen concentrations would experience a change in proton motive force or electron transfer rates 15,46 , resulting in increased motor reversals.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In equilibrium conditions, cells showed a reversal frequency of 0.126 s À 1 or less, which is low compared with data reported for non-MTB [40][41][42][43] . Consistent with the adaptation of MTB for growth in redox gradients in stratified sediments 27 , and also with the dependence of oxygen-sensitive magnetite biomineralization and N 2 fixation on suboxic conditions 44,45 , we found a higher proportion of cells swam faster and reversed less frequently under microoxic than under anoxic or fully oxic conditions. The model of energy taxis suggests cells swimming towards lower or higher oxygen concentrations would experience a change in proton motive force or electron transfer rates 15,46 , resulting in increased motor reversals.…”
Section: Discussionsupporting
confidence: 88%
“…However, as previous observations indicated that magnetospirilla freshly isolated from environmental samples displayed strong swimming polarity 26,27 , we tested whether polarity could be reinduced in our M. gryphiswaldense WT lab strain 28 , which has been passaged for many generations in the absence of magnetic selection. We therefore performed serial transfers of cells in oxygen gradients (Ox Low -Ox High ), exposing them to either parallel (north polesouth pole) or antiparallel (south pole'north pole) magnetic fields of approximately 10 Â the geomagnetic field strength (0.57 mT) ( ¼ selective conditions, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetosome concentrations in sediments also serve as paleoclimate proxies (11)(12)(13)(14). As they contain 2 to 4% (dry weight) Fe (15,16), MTB could influence iron cycles in nature by acting to sequester Fe in sediments (17). Several studies have addressed the spatiotemporal variation of MTB along vertical profiles (16,18,19), yet much less is known about how their horizontal distribution varies in space and time.…”
mentioning
confidence: 99%
“…As they contain 2 to 4% (dry weight) Fe (15,16), MTB could influence iron cycles in nature by acting to sequester Fe in sediments (17). Several studies have addressed the spatiotemporal variation of MTB along vertical profiles (16,18,19), yet much less is known about how their horizontal distribution varies in space and time. Specifically, we question how well MTB populations measured in a given place (a spatial niche) represent a particular environment through time; e.g., do the populations remain fixed in a limited area, move randomly from place to place, or some combination of the two, and over what time scales?…”
mentioning
confidence: 99%